Efficacy of bivalent vaccine against black body syndrome (BBS) of barramundi Lates calcalifer B. - Nugrahawati, Anis; Nuryati, Sri; Sukenda, Sukenda; Rahman, Rahman; Brite, Margie; Aditya, Tiya Widi (Jurnal Akuakultur Indonesia, 2019)
ABSTRACT Black body syndrome causes mass mortality in barramundi (Lates calcarifer) in Asia mariculture. This study aimed to evaluate the efficacy of bivalent vaccine derived from local isolate for black body syndrome (BBS) prevention on the Barramundi. The bacteria used in the bivalent vaccine were Pseudomonas stutzeri and Vibrio harveyi in a ratio of 50:50. Barramundi, 5‒6 cm in length, was intraperitoneally injected with bivalent vaccine and phosphate buffer saline (PBS). After a 21-day vaccination, fish was injected with pathogenic bacteria P. stutzeri, V. harveyi, the combination of P. stutzeri and V. harveyi with a dose of bacteria 107 CFU/fish. We observed relative percent survival (RPS), mortality, blood profile, antibody level, lysozyme activity, and histopathology of vaccinated fish. The result showed that vaccinated fish had higher antibody levels and lysozyme activity than control treatment (P>0.05). Vaccinated fish had RPS of 80.00%, 64.29%, 57.69%, after challenged test with P. stutzeri, V. harveyi, and combination of P. stutzeri and V. harveyi, respectively. Hemoglobin and hematocrit were not significantly different (P>0.05). However, the erythrocytes, leucocytes, and phagocytic activity were higher compared to there were higher erythrocytes, leucocytes, and phagocytic activity compared to control (P<0.05). As well as antibody level and lysozyme activity of vaccinated fish higher than control (P<0.05). In conclusion, the bivalent vaccine of P. stutzeri and V. harveyi could protect barramundi seed from BBS infection. Keywords: Lates calcalifer, bivalent vaccine, local isolate, Pseudomonas stutzeri, Vibrio harveyi                                                                                                                                                                       ABSTRAK Black body syndrome menyebabkan kematian masal pada ikan kakap putih budidaya air laut di wilayah Asia. Tujuan dari penelitian ini adalah untuk menguji efikasi vaksin bivalen untuk penanggulangan black body syndrome pada benih ikan kakap putih. Bakteri yang digunakan untuk membuat vaksin bivalen yaitu Pseudomonas stutzeri dan Vibrio harveyi dengan rasio 50:50. Ikan kakap putih berukuran 5‒6 cm diinjeksi vaksin bivalen dan phosphat buffer saline secara intraperitoneal. Setelah 21 hari pemeliharaan, benih diuji tantang dengan bakteri patogen P. stutzeri, V. harveyi, campuran P. stutzeri dan V. harveyi dengan kepadatan bakteri sebesar 107 CFU/ikan. Parameter yang diamati meliputi relative percent survival (RPS), gambaran darah, titer antibodi, aktifitas lisosim, dan gambaran histopatologi benih kakap putih. Hasil penelitian menunjukkan bahwa ikan yang divaksin memiliki nilai titer antibodi dan aktifitas lisosim lebih tinggi dibandingkan kontrol (P<0.05). Ikan yang divaksin memilki RPS 80.00%, 64.29%, 57.69%, setelah diuji tantang dengan P. stutzeri, V. harveyi, campuran P. stutzeri dan V. harveyi. Nilai hemoglobin dan hematokrit tidak berbeda nyata (P>0.05). Titer antibodi dan aktifitas lisosim ikan yang divaksin lebih tinggi dari kontrol (P<0.05). Vaksin bivalen P. stutzeri dan V. harveyi dapat melindungi benih ikan kakap putih dari infeksi BBS. Kata kunci : Lates calcalifer, vaksin bivalen, Pseudomonas stutzeri, Vibrio harveyi